Key Pathway Analysis of Hospital Engineering Cost Control Based on Whole-Process Management - Xu, Yongbo (Journal of Progress in Civil Engineering, 2025)
This paper proposes a full life cycle management system in view of the common problems existing in the current hospital engineering management. Combined with the characteristics of hospital engineering management in the decision-making stage, design stage, bidding and tendering stage, construction stage and completion acceptance stage, it builds the key point identification and control of the full life cycle and proposes a system guarantee system. The research suggests that hospitals should enhance the identification and construction of risks throughout the entire process, and establish a more complete engineering management database to form a collaborative mechanism in terms of systems, so as to promote the effective management of various risks. The cost management throughout the entire life cycle requires hospitals to break through the traditional static thinking when conducting cost project control, form a dynamic control pattern, eliminate the binary opposition model between Party A and Party B, form a collaborative management system, reduce the negative impact brought by construction changes, and improve the accuracy of cost management.